Centenarios, siglo XXI - Diego Suárez Quevedo (Anales de Historia del Arte, 2003)
Comentaries-remembrances about centenaries in 2001, 2002 and 2003. Competition for the second gates of the Baptistery of Florence (1401), the Bramante’s Tempietto of San Pietro in Montorio in Rome (1502) and the births of the painters Parmigianino and Bronzino (1503).